Reducing DNA extraction costs through factorial design for the DNAdvance Kit - Carson J. Neal; Zachery D. Zbinden; Michael E. Douglas; Marlis R. Douglas (BMC Research Notes)
Abstract Objective Extracting DNA is essential in wildlife genetic studies, and numerous methods are available. However, the process is costly and time-consuming for non-model organisms, including most wildlife species. Therefore, we optimized a cost-efficient protocol to extract DNA from the muscle tissue of White-tailed Deer using the DNAdvance kit (Beckman Coulter), a magnetic-bead-based approach. We devised a 3 × 3 factorial design using combinations of tissue mass (10 mg, 50 mg, or 100 mg) and reaction volume (25%, 33%, and 50% of the manufacturer's recommended volumes). DNA was extracted for N = 81 tissue sub-samples (9 replicates/treatment). Results Our target yield was 500 ng of genomic DNA per sample, sufficient for population genetic assessments. A combination of 50 mg tissue and 25% reaction volume yielded enough DNA at the lowest cost. The factorial design revealed that varying tissue mass and reagent volume significantly affected extracted DNA yield. Our study demonstrates that sufficient DNA can be extracted at 75% lower costs than the manufacturer's standard protocol. Other researchers can directly use our modified DNAdvance protocol to perform cost-effective DNA extractions.